2020
DOI: 10.13189/ujer.2020.081035
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Communication Profile in Solving Probability Problems Reviewed by Self-efficacy of Prospective Mathematics Teachers

Abstract: Mathematical communication plays a very important role in learning mathematics, so it needs to be developed in mathematics learning. Mathematical communication is the process of conveying mathematical ideas to obtain a shared understanding between those who give and receive information. This study aims to describe the mathematical communication profile of prospective mathematics teachers based on self-efficacy in solving probabilistic problems. By solving probabilistic problems, it can improve probabilistic th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
1
4
0
4
Order By: Relevance
“…Students' knowledge of probabilistics and personality in the form of self-regulated learning is a factor that influences probabilistic thinking. This follows the findings of a study conducted by Shodiqin et al (2021). The research shows that the probabilistic level of prospective teacher students is still at level 2 for those with middle-level self-regulated learning.…”
Section: Probabilistic Thinkingsupporting
confidence: 87%
See 2 more Smart Citations
“…Students' knowledge of probabilistics and personality in the form of self-regulated learning is a factor that influences probabilistic thinking. This follows the findings of a study conducted by Shodiqin et al (2021). The research shows that the probabilistic level of prospective teacher students is still at level 2 for those with middle-level self-regulated learning.…”
Section: Probabilistic Thinkingsupporting
confidence: 87%
“…The large amount of information currently expressed in terms of uncertainty has resulted in the importance of probabilistic thinking abilities. Previous research related to probabilistic thinking centered on determining the level of probabilistic thinking at various levels of education, starting from elementary school to college (Fa'ani et al, 2016;Raya, 2017;Raya et al, 2021;Sari et al, 2023;Sari et al, 2017;2018a;Shodiqin et al, 2021;. The research results found that students' probabilistic thinking tends to be low and is often at a level below their age.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…seseorang menyelesaikan permasalahan (Shodiqin et al, 2021). Kemampuan berpikir seseorang dapat dipengaruhi oleh pengalaman atau kerangka teori yang diterima di sekolah maupun di tempat lain (Madawistama et al, 2022).…”
unclassified
“…Terdapat enam konstruksi utama dalam berpikir probabilistik, yakni: mengonstruk ruang sampel, peluang suatu kejadian, peluang perbandingan, peluang bersyarat, peluang satu kejadian dan peluang dua kejadian (Jones et al, 1999;Shodiqin et al, 2021). Dalam berpikir probabilistik terdapat empat level berpikir, yakni: level 1 (subjective), level 2 (transitional), level 3 (quantitative informal), dan level 4 (numerical) ( Hodiyanto & Oktaviana, 2018;Jones et al, 1999;Taram, 2016).…”
unclassified